The Codebreakers. : 2 On wings of devotion - Roseanna M. White (Minneapolis : Bethany House, 2020)
"All of England thinks Phillip Camden a monster - a man who deliberately caused the deaths of his squadron. But as nurse Arabelle Denler watches the so-dubbed 'Black Heart' every day, she sees something far different: a hurting man desperate for mercy. And when their paths twist together and he declares himself her new protector, she realizes she has her own role to play in his healing" -- Provided by publisher
Keywords: Christian fiction; Great Britain; Code and cipher stories